Distal Symmetric Polyneuropathy Pain in Diabetes Mellitus - Daniella Silva Oggiam; Juliana Vallim Jorgetto; Guilherme Luiz Chinini; Denise Myuki Kusahara; Mônica Antar Gamba (Universidad de La Sabana, 2021)
Objective: To evaluate neuropathic pain (NP), its intensity, and complications in people with type 2 diabetes mellitus (T2DM) in a city of eastern São Paulo. Method: Cross-sectional study conducted with 96 individuals with T2DM served by primary health units in São João da Boa Vista-SP. The following instruments were used to screen NP: Michigan Neuropathy Screening Instrument, Leeds Assessment of Neuropathic Symptoms and Signs, Douleur Neuropathique 4, and Brief Pain Inventory. The data were analyzed using descriptive and inferential statistics, with a 5 % significance level. Results: Of the 96 people with T2DM for longer than five years, 22.9 % had pain. NP was related to high levels of fasting blood glucose (mean = 214 ± 65.58 mg/dl; p = 0.0002), glycated hemoglobin (mean = 8.8 ± 0.11 %; p < 0.001), absence of a balanced diet (p = 0.0066), obesity (p = 0.023), and high blood pressure (p < 0.001). Conclusion: Higher values ​​of glycated hemoglobin rates increased three times the chance of NP. The screening and management of painful diabetic neuropathy is a challenge but adopting a screening protocol supports the secondary prevention of this manifestation.